Sorbitol MacConkey agar and wastewaters` coliphages - Tesfaye Bedada; Teshome Eshete; Adey Desta; Fitsum Yifat; Dagim Birri; Kassu Tullu; Samson Gebre; Firehiwot Dera; Kaleab Awoke; Tatek Feto; Waktole Sima; Elias Deribe; et al. (Journal of Applied Research in Water and Wastewater, 2023)
A total of 114 samples collected from hospital wastewaters and rivers in Addis Ababa, Ethiopia were tested for non-sorbitol fermenting bacteria and coliphages. Sorbitol MacConkey agar is mainly used in the detection of E. coli O157:H7. However, other emerging diarrhoeagenic enteropathogens such as Plesiomonas shigelloides, Edwardsiella tarda, Providencia alcalifaciens, Escherichia albertii, Escherichia vulneris and Escherichia fergusonii were detected in the samples using this medium. Information for most of the emerging enteropathogens is scarce in most countries including Ethiopia. A total of 20 different genera, 38 species of non-sorbitol fermenting bacteria were isolated. Escherichia coli O157 could not be detected from any of the samples. All these backgrounds may mask the detection of Escherichia coli O157. Even if sorbitol MacConkey agar has several background limitations, different emerging diarrhoeagenic non-sorbitol fermenting bacteria were detected in the majority of the rivers and hospitals` wastewaters samples. The correlation between coliphages and non-sorbitol fermenting bacteria were not significant. As several bacteria have been isolated on sorbitol MacConkey agar medium, it is essential that the most selective laboratory techniques will be desired for outbreak investigation of E. coli O157, but other non-sorbitol fermenting enteropathogens should also be detected using sorbitol MacConkey agar in low resources countries.